A Study to Assess the Effectiveness of Facilitated Tucking Position on Pain Perception among Neonates During Vaccination in Selected Hospital of Panipat, Haryana (International Journal of Nursing Education, 2021)
Background and Objective: A study was done to assess the effectiveness of facilitated tucking position onpain perception among neonates during vaccination in selected hospital of Panipat. Material & Methods:The methodology of the present study was true experimental research design. Sample size of the study was60 neonates during vaccination selected with random sampling technique. 30 neonates in each group washeld in the facilitated tucking position & in routine care during Hepatitis B vaccination. NIPS was used fordata collection. Data collection method was interview & observation method; data analysis was done withthe help of descriptive and inferential statistics. Result: The mean pain scores of neonates vaccinated in thefacilitated tucking position (2.53±1.042) were significantly statistically lower than the scores of neonatesvaccinated in the routine position (5.80±0.925) (p
Keywords: Facilitated tucking position, Neonates, Pain perception & Vaccination.